NEW AGRICULTURAL POLITICS IN TURKEY: THE ECONOMETRIC ASSESSMENT OF COTTON PRODUCTION AND YIELD 1925 – 2015 - K. Karadas1; S. Celik; S. Hopoglu; E. Eyduran; F. Iqbal (Journal of Animal and Plant Sciences, 2017)
This study was conducted to evaluate causality between long-term relationships among production amount, cultivated area and yield of cotton lint for Turkey for the period 1925 to 2015, and to determine the strength and direction of the relationships by means of vector error correction model (VECM) and cointegration analysis. After taking the first differences of the original (non-stationary) time series data on cotton lint, stationary time series data were obtained and exposed to cointegration analysis to determine whether any long-term relationships among the variables exist and whether the series were integrated. Both production amount and cultivated area had a positive effect on yield. The effect of production amount on yield is more than that of cultivated area. In order to find the direction of the long term relationship and the short term effects, vector error correction model (VECM) analysis was used and the analysis presented evidence of a causality relationship between cotton production and yield in Turkey. Holt exponential smoothing method was used to forecast cultivated area, amount of production, and yield from the period 2016 – 2026. The results of Holt method revealed that cultivated area, amount of production, and yield are expected to increase for the above-mentioned time period. New agricultural policies should be formulated in order to cut back on an estimated 20 billion dollars forecasted to be spent on cotton imports between 2016 and 2026.
Keywords: Cointegration; vector error correction model; exponential smoothing method; cotton; production economics